From metaphoric litany text to scenarios—How to use metaphors in futures studies. (November 2016) - Kuusi, Osmo; Lauhakangas, Outi; Ruttas-Küttim, Ruuta
Highlights: The article discusses metaphors in the frame of the CLA. The main research question is the following: how to use the CLA in the critical analysis of litany texts. Litany in our textual CLA is a specific written, spoken or pictorial text that anticipates the future or suggests future relevant action(s). The text specific CLA assumes that the litany text includes other level metaphors: The textual CLA analyses written, spoken or pictorial litany texts and their metaphors on three CLA levels. Second level metaphors of the litany text try to avoid many interpretations like metaphors used in mathematics. Third or worldview level metaphors illustrate rational systemic generalizations. Fourth level metaphors of the litany text are emotionally ladded or mythic. As illustrating example, we analyse a litany text about the Northern Sea Route. Looking at common sayings or proverbs concerning trust, the article discusses study methods suitable for the textual version of the CLA.The example litany text concerns the Northern Sea Route. Abstract: Metaphor and metonymy belong to the key concepts of semiotics and general linguistics. As illustrations of scenarios, metaphors already have a long history in the futures studies, too. Metaphors were discussed in the CLA Reader 1.0 1 (Inayatullah ed., 2004 ) but the CLA Reader 2.0 edited byInayatullah and Milojevic (2015) gives metaphors the central role in futures research 2 that they deserve. The article compares the approaches of semiotics and the CLA and suggests practical steps for the analysis of metaphoric futures oriented texts and their use in the construction of scenarios. Assuming that the litany is a text, metaphors may be present on all levels of the CLA: litany, systemic causes, worldview and myth/emotion. Metaphors are suitable even for the illustration of the CLA second level quantitative causal relations between variables. As an illustrating case study, we analyze a text that suggests the great future of the Northern Sea Route. The deconstruction of the litany results in two narratives or scenarios. They are constructed utilizing proverbs and other metaphoric sayings that get many citations on the Internet.